(untitled) (International Journal of Innovative Technologies in Economy, 2018)
In a modern stage of national economic unit-intertwine conditions the process of transnationalization and internationalizations concern to every country, including Georgia. Transnazionalization, as a process the important subjects are transnational companies, their business in different countries supports to develop national economy and to integrate faster in international economic system. Transnational corporations are determined as an important resource flow of foreign direct investments. Transnational corporations play important role within the current global economy. They have larger budget than small countries. Transnational corporations also contribute significantly to individual nations through foreign direct investment, creating thousands of jobs and investing in the companies’ infrastructure. In a modern stage of national economic unit-intertwine conditions the process of transnationalization and internationalizations concern to every country, including Georgia. After recovery of independency Georgia started to involve in a globalization process and implemented important economic reforms.